Comparing the Relationship of Emotional Intelligence and General Health in Nurses of Intensive Care Units With General Units in Qazvin - Leili Yekefallah; Leila Dehghankar; Mahya Shafaei; Fereshteh Yekefallah (Shahrekord University of Medical Sciences, 2019)
Background and aims: To know that how emotional intelligence and general health are related, can play a crucial role in the quality of nurses' performance. The present study was conducted to compare the relationship of emotional intelligence and general health in nurses of intensive care units with other units in Qazvin city, Iran. Methods: This cross-sectional study was conducted among nurses working in hospitals of Qazvin in 2018. To this end, 250 nurses were selected by random sampling. Data collection tool was Goldberg General Health Standard Questionnaire (GHQ) and Shearing's Emotional Intelligence Questionnaire (EIQ). Data were analyzed by SPSS statistical software version 18.0 using the statistical tests of Pearson correlation, t test, ANOVA, chi-square, and liner regression. A P value less than 0.05 was also considered statistically significant. Results: The mean score of general health was 21.33 ± 10 and the mean score of emotional intelligence was 122.8 ± 11.5. The findings showed that there was a statistically significant relationship between emotional intelligence and general health and all general health components (P <0.05). Level of depression in Intensive Care Unit was higher than that in other units (P <0.05). Moreover, according to linear regression coefficient, there was a statistically significant association between general health and emotional intelligence (P <0.05), to such a degree that increasing emotional intelligence caused an increase in general health. This model identified 5.6% of health variance, emotional intelligence, and body mass index (BMI) variables as predictive variables. Conclusion: Considering the fact that nursing is a stressful profession, attention to emotional intelligence is very effective and valuable in improving mental health and as a result, in reducing job stress, increasing the quality of nursing care, reducing burnout, and ultimately increasing patient satisfaction from nursing care.